119k views
4 votes
Evaluate f(x)=-x^-4 for x=3

2 Answers

4 votes

Answer:

-
(1)/(81)

Explanation:

Using the rule of exponents


a^(-n)
(1)/(a^(n) )

Hence

f(3) =-
3^(-4) = -
(1)/(3^(4) ) = -
(1)/(81)

User Dinodsaurus
by
4.3k points
2 votes

The answer would be -0.012345679.

The first thing you would do is substitute 3 in for x, seeing that you've told us x = 3. After you've substituted x, the equation would look something like:

f(3) = -3^-4. From here, all you have to do is solve! -3 to the power of -4 equals -0.012345679. Therefor, f(3) = -3^-4 equals -0.012345679

User Andriy Gordiychuk
by
4.7k points